2004
DOI: 10.1021/ie034274h
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Hydrogen-Terminated Silicon with Polybetaine Brushes via Surface-Initiated Reversible Addition−Fragmentation Chain-Transfer (RAFT) Polymerization

Abstract: Controlled grafting of polybetaine brushes onto hydrogen-terminated Si(100) substrates (Si-H substrates) was carried out via surface-initiated reversible addition-fragmentation chain-transfer (RAFT) polymerization. The azo initiator was immobilized on the Si-H surface through a threestep process: (i) coupling of an ω-unsaturated alkyl ester to the Si-H surface under UV irradiation, (ii) reduction of the alkyl ester into a hydroxyl group by LiAlH 4 , and (iii) esterification of the hydroxyl group with the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 47 publications
(107 reference statements)
3
58
0
Order By: Relevance
“…[228] Most work has used ATRP or NMP, though papers on the use of RAFT polymerization have begun to appear. [229][230][231][232][233][234][235] The first to apply RAFT in this context were Tsujii et al [229] and Brittain and coworkers. [230,231] Recent papers describe RAFT polymerization from plasma-treated Teflon surfaces [232] and ozonolyzed polyimide films.…”
Section: Microgelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[228] Most work has used ATRP or NMP, though papers on the use of RAFT polymerization have begun to appear. [229][230][231][232][233][234][235] The first to apply RAFT in this context were Tsujii et al [229] and Brittain and coworkers. [230,231] Recent papers describe RAFT polymerization from plasma-treated Teflon surfaces [232] and ozonolyzed polyimide films.…”
Section: Microgelsmentioning
confidence: 99%
“…[230,231] Recent papers describe RAFT polymerization from plasma-treated Teflon surfaces [232] and ozonolyzed polyimide films. [235] The approach used in these and most other studies [230][231][232][233][234][235] has been to immobilize initiator functionality on the surface by chemical or plasma modification and use this to initiate polymerization in the presence of a dithioester RAFT agent. Tsujii et al [229] have indicated that some difficulties arise in using RAFT for grafting from particles because of an abnormally high rate of radical-radical termination caused by a locally high concentration of RAFT functionality.…”
Section: Microgelsmentioning
confidence: 99%
“…The living character of this polymerization was demonstrated by the reinitiation of the polymer chains. The same strategy was used by Zhai et al [208] to grow polyelectrolyte brushes (polybetaine) from the surface-immobilized azoinitiator (silicon wafer).…”
Section: Raftmentioning
confidence: 99%
“…The design, synthesis and development of new functional materials were studied to provide suitable materials for biomedical applications such as polyacrylate, polyester, polyurethane, polyamide, polyimide, polyester, polynorborene, polytetrafluoroethylene, polydiphenylacetylenes and polymeric resins . Also, surface modification technology was considered to change the surface microenvironment of the materials [22][23][24][25][26]. Therefore, a suitable material and fabrication process can be selected, designed and established.…”
Section: Introductionmentioning
confidence: 99%